Development of the Social Experience of a Concert Scales (SECS): The Social Experience of a Live Western Art Music Concert Influences People's Overall Enjoyment of an Event but not Their Emotional Response to the Music. (June 2022) - O'Neill, Katherine; Egermann, Hauke
Social experience is often considered to be a key motivating factor for engaging with leisure activities and attendance at music concerts is no exception. Despite this, until recently, there has been limited interest in measuring the collective or social experience of live concerts in a quantitative way. Therefore, we created and validated a new measure of the social experience of a concert. In a pilot study, 103 participants were recruited across two concert settings . An extensive list of 65 items was used to measure the social experience of a concert. Based on the results, the measurement scale was reduced to 22 items. In the main study, a further 113 participants were recruited at several concerts from a weekly series with a range of musical genres. Participants provided self-ratings of their social experience, emotional response (GEMIAC), enjoyment and demographic information in a paper survey. Based on the results of exploratory and confirmatory factor analysis we were able to reduce the number of items in the Social Experience of a Concert Scales (SECS) to 17 validated statements representing a five-factor model: Depth of Processing, Attention, Solidarity, Satisfaction, and Self-Definition. Using MANOVA, we tested the influence of these factors on the emotional response of participants to the music and found that they are not significant predictors; however, the social experience of a concert was found to be a significant predictor of enjoyment. We have developed and validated the first quantitative measure of the social experience of a Western art music concert. Our results also suggest that the emotional response to music and the overall experience of a concert are separate and that only the latter can be influenced by the social experience of a concert.